2022
DOI: 10.3390/systems10040120
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Impacts of COVID-19 on Coastal Tourism to Inform Recovery Strategies in Nelson Mandela Bay, South Africa

Abstract: Globally, the COVID-19 pandemic bought devastating impacts to multiple economic sectors, with a major downfall observed in the tourism sector owing to explicit travel bans on foreign and domestic tourism. In Nelson Mandela Bay (NMB), South Africa, tourism plays an important role; however, negative effects from the pandemic and resulting restrictions has left the sector dwindling and in need of a path to recovery. Working together with local government and stakeholders, this study applied system dynamics modell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Safarrad et al ( 57 ) analyzed the impact of tourism on LST and found that the LST between tourist areas and other regions was significantly different. In addition to the changes in natural elements, tourism is usually accompanied by a large inflow of people into the designated islands, during which, a large amount of anthropogenic heat will also be generated, resulting in heat discomfort, which will negatively impact the physiology and psychology of tourists ( 28 , 58 ). Whereas, tourists usually stay in tourist areas for a specific period of time, the state of the environment is critical to the sustainability of the local area for those living on the island for long periods of time, and it is shown in chapter 3.2 that forests are the most vulnerable surface type, and that forests have a significant effect on cooling.…”
Section: Discussionmentioning
confidence: 99%
“…Safarrad et al ( 57 ) analyzed the impact of tourism on LST and found that the LST between tourist areas and other regions was significantly different. In addition to the changes in natural elements, tourism is usually accompanied by a large inflow of people into the designated islands, during which, a large amount of anthropogenic heat will also be generated, resulting in heat discomfort, which will negatively impact the physiology and psychology of tourists ( 28 , 58 ). Whereas, tourists usually stay in tourist areas for a specific period of time, the state of the environment is critical to the sustainability of the local area for those living on the island for long periods of time, and it is shown in chapter 3.2 that forests are the most vulnerable surface type, and that forests have a significant effect on cooling.…”
Section: Discussionmentioning
confidence: 99%
“…This study reports on the qualitative modelling phase that was undertaken to understand the impacts of COVID-19 on tourism in NMB (Figure 3). More information on the quantitative modelling steps is available in [44], which builds off a broader SDM process to support coastal and marine management in NMB as reported in [50].…”
Section: Methodsmentioning
confidence: 99%
“…This study reports on the qualitative modelling phase that was undertaken to understand the impacts of COVID-19 on tourism in NMB (Figure 3). More information on the quantitative modelling steps is available in [44], which builds off a broader SDM process to support coastal and marine management in NMB as reported in [50]. During the participatory process, a series of online meetings and workshops were held to explore the dynamics behind "the impacts of COVID-19 on coastal tourism in NMB".…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…While the South African government's response to COVID-19 began in March 2020, with the implementation of the national lockdown, the MICE sector (along with other typologies of events) had already cancelled and postponed their events much earlier (Hemmonsbey et al, 2021;. The national COVID-19 response had been followed by the adoption of the Alert Level strategy to manage the reopening of certain sectors while accounting for the state of the virus in the country; the level of infections and transmission rates at the time, health facilities capacities and socio-economic impacts of the restrictions (Bama and Nyikana, 2021;GSA, 2021;Kotze, 2021;Vermeulen-Miltz et al, 2022). Since the MICE sector was classified within 'gatherings' under the Disaster Management Act, the sector was particularly vulnerable to regulations pertaining to the number of people permitted at gatherings and international borders (Bartis et al, 2020;TBCSA, 2020).…”
Section: South Africa's Mice Sector's Response To Covid-19mentioning
confidence: 99%